Measurement of B-s(0) meson production in pp and PbPb collisions at root S-NN=5.02 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Elsevier B.V., 2019)
The production cross sections of B0 s mesons and charge conjugates are measured in proton-proton (pp) and PbPb collisions via the exclusive decay channel B0 s → J/ψφ → μ+μ−K+K− at a center-of-mass energy of 5.02 TeV per nucleon pair and within the rapidity range |y| < 2.4 using the CMS detector at the LHC. The pp measurement is performed as a function of transverse momentum (pT) of the B0 s mesons in the range of 7 to 50 GeV/c and is compared to the predictions of perturbative QCD calculations. The B0 s production yield in PbPb collisions is measured in two pT intervals, 7 to 15 and 15 to 50 GeV/c, and compared to the yield in pp collisions in the same kinematic region. The nuclear modification factor (RAA) is found to be 1.5 ± 0.6(stat) ± 0.5(syst) for 7–15 GeV/c, and 0.87 ± 0.30(stat) ± 0.17(syst) for 15–50 GeV/c, respectively. Within current uncertainties, the B0 s results are consistent with models of strangeness enhancement, and suppression by parton energy loss, as observed for the B+ mesons.